The Use of Peer Feedback in Teaching Writing Procedure Text at High School - Alfinia, Fitria Maya; Masrupi, Masrupi; Hamer, Welliam (Journal of Linguistics, Literacy, and Pedagogy, 2024)
This study aims to investigate the implementation and response of students on peer feedback at a high school of SMA Informatika Kota Serang. The researcher used qualitative research with a case study method. Observation, questionnaires, and interviews were used as the data collecting technique. The subject of this research were tenth grade students, which consisted of 18 students. Based on the findings, it was found that the implementations were implemented in stages as:1)pre-training stage,2)while editing stage,3)post-editing stage. Students were training their critical thinking as well as communication skills as they exchanged the paper with their peers. This way, students are able to know their mistakes. The teacher also supervises peer feedback activity in class, making sure the teacher rechecks students' work after receiving comments from their peers. Additionally, based on the students’ response towards peer feedback, it has been found that students responded positively towards peer feedback activity. Students found it helpful and fun. They gain new knowledge from being the reviewer and the comments receiver. The students were enthusiastic in using peer feedback in the classroom. Thus, the researcher concludes that the implementation by the teacher was easy to follow and students reacted positively towards the usage of peer feedback in helping them make procedure text.